﻿Study on species diversity of Akanthomyces (Cordycipitaceae, Hypocreales) in the Jinyun Mountains, Chongqing, China - Wan-Hao Chen; Jian-Dong Liang; Xiu-Xiu Ren; Jie-Hong Zhao; Yan-Feng Han (MycoKeys, 2023)
Akanthomyces species have only been reported from Guizhou and Qinghai Province, with few reports from other regions in China. In this research, the species diversity of Akanthomyces in the Jinyun Mountains, Chongqing was investigated. Fourteen infected spider specimens were collected and two new species (A. bashanensis and A. beibeiensis) and a known species (A. tiankengensis) were established and described according to a multi-locus phylogenetic analysis and the morphological characteristics. Our results reveal abundant Akanthomyces specimens and three species were found at Jinyun Mountain. Due to its being an important kind of entomopathogenic fungi, further attention needs to be paid to the diversity of other entomopathogenic fungi in Chongqing, China.